NERGY GENERATING TILE, AS ALTERNATIVE LOW-POWER SOURCE OF ELECTRIC ENERGY - A. Gnatov; Sch. Argun (Avtomobilʹnyj Transport (Harʹkov), 2017)
Analysis of existing developments such as the alternative power sources transforming different types of energy into electric energy is carried out. The technical solution for the installation of energy-generating plates, which converts the kinetic energy from pressure into electric and accumulates it for further use is suggested. The principle of action of energy-generating tiles as an alternative and decentralized source of electric energy is discussed in detail and described.